Ruderal vegetation of Ukraine: Stellarietea mediae Tx. et al. in Tx. 1950 - Dubyna, Dmytro; Iemelianova, Svitlana; Dziuba, Tetiana; Davydova, Anastasia; Davydov, Denys; Tymoshenko, Pavlo (Biodiversity: Research and Conservation, 2022)
Between 2015 and 2020 a study was conducted on the diversity of ruderal vegetation of the Stellarietea mediae class on the territory of Ukraine. It was discovered that this class consists of 48 associations from 12 alliances and 5 orders (Aperetalia spicae-venti, Atriplici-Chenopodietalia albi, Eragrostietalia, Papaveretalia rhoeadis, Sisymbrietalia sophiae). Based on the results of ordination analysis it was found that the distribution of annual ruderal communities is determined by the variation of moisture, soil aeration as well as carbonate and nitrogen content.